Superior Sagittal Sinus Thrombosis Secondary to Cerebral Aspergillosis with Ventriculitis in an Immunocompetent Patient: A Case Report - Chaisawasthomrong, Chonnawee (Asian Journal of Neurosurgery, 2024)
Cerebral aspergillosis is an opportunistic fungal infection that is exceedingly rare in immunocompetent patients. The primary etiological locations for these infections typically involve the nasal cavity and hematological dissemination. A 62-year-old male, focused on wellness, presented with intermittent, nonprogressive headaches in the occipital region, generalized clonic–tonic seizures, and altered consciousness. A computed tomography scan revealed multiple small rim-enhancing lesions in both occipital lobes, with vasogenic edema in both occipital lobes adjacent to the confluence of the sinuses and the posterior superior sagittal sinus. In this case, superior sagittal sinus thrombosis secondary to cerebral aspergillosis was discovered, a condition not previously diagnosed in this specific location but manageable through surgical intervention. A combination of surgical resection and antifungal therapy resulted in favorable outcomes. The prognosis for patients depends significantly on early diagnosis and prompt, aggressive treatment.
Keywords: superior sagittal sinus thrombosis; venous sinus thrombosis; cerebral aspergillosis; brain abscess; aspergillosis